Effects of long and short ejaculatory abstinence on sperm parameters: a meta-analysis of randomized-controlled trials - Lo Giudice, Arturo; Asmundo, Maria Giovanna; Cimino, Sebastiano; Cocci, Andrea; Falcone, Marco; Capece, Marco; Abdelhameed, Ali Saber; Capogrosso, Paolo; Morgado, Afonso; Tsampoukas, Georgios; Manfredi, Celeste; Russo, Giorgio Ivan (Frontiers in Endocrinology, 2024)
Purpose: To investigate whether ejaculatory abstinence would affect sperm parameters.Methods: This analysis has been registered on PROSPERO (CRD42023472124). We performed a search on Pubmed using the following text terms: (("sperm parameters" OR "sperm analysis"[Mesh]) AND ("sperm DNA fragmentation" OR "DNA fragmentation" [Mesh]) AND ("sexual abstinence" [Mesh] OR "abstinence")) and an advanced search in Scopus using the terms ("sperm parameters" OR "sperm parameters" OR "DNA fragmentation") AND ("abstinence"). Sperm parameters that have been investigated were sperm volume, total sperm motility, progressive sperm motility, sperm concentration, sperm morphology and sperm DNA fragmentation (SDF). A two-day cut-off as a "short" or "long" abstinence period has been defined.Thirteen studies published between 2013 and 2022 have been included in the metaanalysis. In total, 2315 patients, ranging from 6 to 836 from each cohort, have been enrolled in the study. We showed that longer abstinence time was associated with greater sperm concentration (mean difference [MD]: 8.19; p<0.01), sperm volume (MD: 0.96; p<0.01) and higher SDF (MD: 3.46; p<0.01) but lower progressive sperm motility (MD: -1.83; p<0.01). Otherwise, a not statistically significance difference was observed in patients with longer vs. shorter abstinence time regarding total sperm motility (MD: -1.83; p=0.06). Meta-regression analysis showed that days of abstinence were positively and linearly related to sperm concentration (slope: 3.74; p<0.01) and SDF (slope: 0.65; p=0.044).Conclusions: According to our data, short ejaculatory abstinence is associated with better sperm quality; indeed, higher percentage of progressive sperm motility and lower level of SDF were reported in short abstinence cohort. Otherwise, long abstinence group reported higher sperm concentration.